Labor Market Returns to a Prison GED - Rajeev Darolia; Peter R. Mueser; Jacob Cronin (Institute of Labor Economics (IZA), 2020)
Educational and skill-building programs are commonplace in prisons and have been the focus of recent prominent policy initiatives. These educational programs are expected to increase prisoners' post-release employability, with the hope that these lead to both private and public benefits. One of the most popular programs prepares prisoners to pass the GED exam, which is an academic certification for those without a high-school diploma. We analyze the labor market returns to a GED earned in prison using new administrative data on all released prisoners in the state of Missouri over nearly 25 years, and a matched comparison group difference-in-differences design with individual fixed effects. We find that the GED can lead to higher short-term quarterly earnings and employment, with the largest benefits experienced soon after release. These effects are strongest for those who did not have strong work histories prior to entering prison and for those who had access to post-release support. We also find that the effect of the GED is of a similar magnitude for White and Black formerly incarcerated individuals.
Keywords: I26; J24; J31; J38; 330; GED; prison; incarceration; returns to education